On-machine calibration of angular position and runout of a precision rotation stage using two absolute position sensors. (1st March 2020) - Kim, Jong-Ahn; Kim, Jae Wan; Kang, Chu-Shik; Lee, Jae Yong; Jin, Jonghan
Highlights: A precision rotation stage was calibrated using two absolute position sensors. Angular position and runout of a rotation stage could be obtained simultaneously. The calibrated angular positions agreed with the reference values within ±1″. The runout was measured with the repeatability of 80 nm and error of 120 nm. The proposed method would be applied to on-machine calibration effectively. Abstract: A calibration method for a precision rotation stage is proposed to evaluate angular position error and runout of the stage with robustness to alignment error and a simple setup. It consists of two absolute position sensors and a two-dimensional (2D) scale. Therefore, it is proper for on-machine calibration where enough install place and fine adjustment might be unavailable. Angular positions are obtained using two coordinate values on the 2D scale fixed on the rotating plate, and the complete runout is calculated by processing these values through Fourier analysis. The calibrated angular positions of a rotation stage agreed with the reference values within ±1″. The proposed system measured runout with the repeatability of 80 nm and error of 120 nm. An effective compensation method for measurement error caused by out-of-plane motion of the rotation stage was discussed and its feasibility was proved though experiments.